Optimalkan Kesehatan Reproduksi Remaja melalui Pelatihan Peer Educator Kesehatan Reproduksi Remaja pada Organisasi Nasyiatul Aisyiyah Kabupaten Pekalongan: Optimizing Adolescent Reproductive Health Through Peer Educator Formation Training at the Nasyiatul Aisyiyah Organization, Pekalongan Regency - Fitriyani, Fitriyani; Susiatmi, Sandi Ari; Risdiani, Risdiani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The problem of reproductive health in adolescents is a complex problem that requires intensive and coordinated handling across programs, sectors, and disciplines that pay attention to local socio-culture. Nasyiatul Aisyiyah (NA) is one of the youth organizations to become a change in the Pekalongan Regency, such as increasing knowledge about adolescent reproductive health, especially preconception premarital preparation. NA adolescent cadres have a big role in helping to increase adolescent knowledge about reproductive health The purpose of this community service is to assist partners in efforts to increase adolescent knowledge about adolescent reproductive health through the training of NA cadres Pekalongan Regency Branch. The method of implementing peer educator formation training for NA cadres is through the introduction of material on adolescent reproductive health peer educators, screening of adolescent nutritional status and premarital adolescent nutrition education, and strengthening adolescent reproductive health in the context of Al Islam. The result of this activity is an increase in partner knowledge about the role of adolescent reproductive health peer educators and the formation of peer educators in skilled NA branch representatives in the Pekalongan Regency. The importance of role of peer educators in adolescent reproductive health in the community is expected to prevent various adolescent reproductive health problems.